PEMBERDAYAAN EKONOMI PEREMPUAN MELALUI MANAJEMEN USAHA KECIL DI DESA KUDUS LUMAJANG - Zainuddin; Ahmad Zarkasyi ('Ibadatuna : Jurnal Pengabdian Masyarakat, 2023)
The article describes women's economic empowerment through small business management. Research using constructive methods. Based on the research results, the economic empowerment of women through small business management in Kudus Village, Lumajang Regency has carried out the following activities: management of small businesses in Kudus Village, Lumajang Regency through a systematic process, starting from preparing tools and materials, packing chips, marketing to Family income budget plan, assistance with receiving and spending family funds. The system of women's economic empowerment through small business management is carried out through evaluation and accountability